What Makes Them Persist? Expectancy-Value Beliefs and the Math Participation, Performance, and Preparedness of Hispanic Youth. (August 2019) - Safavian, Nayssan
This study examined the longitudinal associations of Hispanic youths' 9th-grade math expectancy-values and their subsequent participation (course taking and advanced course taking), performance, and preparedness (high school graduation and university eligibility) across 9th to 12th grades. Gender moderation associations of expectancy-value and participation, performance, and preparedness were evaluated. Students' socio-demographic characteristics and previous math experiences (achievement and curricular track) were controlled. The study sample (n = 1, 116) was 53% female, 46% English learner, and 84% low income. Males reported higher expectancy, interest, attainment, and cost values. Females completed more math courses and advanced courses, achieved stronger course grades, and were more likely to complete math preparation requirements for high school graduation and college. Associations of expectancy-value, and participation and performance were observed along with gender-moderated associations with preparedness. The odds of graduation preparedness were increased for females with high attainment value, whereas the odds of university preparedness were increased for males with high utility value.